Minimizing fall for user suffering from single limb trauma in the toilet - Boay, Kai Xun (Nanyang Technological University, 2022)
This project aims to minimize the probability of falls for users suffering from single limb trauma in the toilet. One of the reason for falls is due to users requiring to hop in the toilet using a walker or crutches when using the toilet. The methods used are identifying design aims, finding pain points, prototyping, user testing, styling, 3D modeling, and product visualization. This project aims to fill the gap in the market that does not provide a comprehensive solution to provide mobility and support for users suffering from single limb trauma in the toilet.